A case of inverted insertion assessed by R and G banding. Issue 2 (April 1982) - Arce, Miguel A De; Law, Elizabeth; Martin, L; Masterson, Joseph G
Abstract : Cytogenetic studies in a 2-year-old boy referred to our laboratory for developmental delay showed an unusual karyotype with a three break rearrangement. R and G banding were both necessary to determine the exact nature of the rearrangement which is described as 46, XY, inv ins(16;3)(q22;p26p13). Several features coincide with the reported description of another patient where 3p26 was missing, and the coincidence is explained as a position effect.